\\\ a=\frac{7\pm11}{6} \\\ a_1=\frac{7+11}{6}=3 \\\ a_2=\frac{7-11}{6}=-\frac{4}{6}=-\frac{2}{3} \\\ tgx_1^2=3 \\\ tgx_1=\pm\sqrt{3} \\\ x_1=\pm\frac{\pi}{3}+\pi n, n\in Z \\\ tgx_2^2\neq-\frac{2}{3} \\\ a^2\geq0" alt="3tg^2x-7=6ctg^2x=\frac{6}{tg^2x} \\\ tg^2x=a \\\ 3a-7=\frac{6}{a} \\\ 3a^2-7a=6, a\neq0 \\\ 3a^2-7a-6=0 \\\ D=49+72=121 \\\ a=\frac{7\pm11}{6} \\\ a_1=\frac{7+11}{6}=3 \\\ a_2=\frac{7-11}{6}=-\frac{4}{6}=-\frac{2}{3} \\\ tgx_1^2=3 \\\ tgx_1=\pm\sqrt{3} \\\ x_1=\pm\frac{\pi}{3}+\pi n, n\in Z \\\ tgx_2^2\neq-\frac{2}{3} \\\ a^2\geq0" align="absmiddle" class="latex-formula">
Ответ: ![x=\pm\frac{\pi}{3}+\pi n, n\in Z x=\pm\frac{\pi}{3}+\pi n, n\in Z](https://tex.z-dn.net/?f=x%3D%5Cpm%5Cfrac%7B%5Cpi%7D%7B3%7D%2B%5Cpi+n%2C+n%5Cin+Z+)
![\sqrt{2x^2+x-5}=x+1, x+1\geq0 \\\ 2x^2+x-5=x^2+2x+1, x\geq-1 \\\ x^2-x-6=0 \\\ D=1+24=25 \\\ x=\frac{1\pm5}{2} \\\ x_1=3 \\\ x_2\neq-2<-1 \sqrt{2x^2+x-5}=x+1, x+1\geq0 \\\ 2x^2+x-5=x^2+2x+1, x\geq-1 \\\ x^2-x-6=0 \\\ D=1+24=25 \\\ x=\frac{1\pm5}{2} \\\ x_1=3 \\\ x_2\neq-2<-1](https://tex.z-dn.net/?f=%5Csqrt%7B2x%5E2%2Bx-5%7D%3Dx%2B1%2C+x%2B1%5Cgeq0+%5C%5C%5C+2x%5E2%2Bx-5%3Dx%5E2%2B2x%2B1%2C+x%5Cgeq-1+%5C%5C%5C+x%5E2-x-6%3D0+%5C%5C%5C+D%3D1%2B24%3D25+%5C%5C%5C+x%3D%5Cfrac%7B1%5Cpm5%7D%7B2%7D+%5C%5C%5C+x_1%3D3+%5C%5C%5C+x_2%5Cneq-2%3C-1)
Ответ: 3